UJI EFEKTIVITAS PERTUMBUHAN Lactobacillus casei PADA MEDIA UMBI GANYONG MERAH DAN GANYONG PUTIH - Aptari, Zahra (JURNAL BIOSHELL, 2021)
One of the bacteria growing media that is often used in laboratories is Nutrient Agar (NA). However, the price of this bacterial growth medium is relatively expensive. The high price of media and the abundance of untapped natural resources have encouraged researchers to find new alternative media from simple ingredients. Tubers contain high carbohydrate content so they have the potential to be used as the medium. This study used Nutrient Agar as a control as well as two varieties of canna tubers (Umbi Ganyong), namely white canna and red canna. This research is an experimental study to determine the effectiveness and characteristics of canna tubers as a medium for bacterial growth, which in this study used three variations of the concentration of canna tuber powder (10, 20, 30) grams per 600 ml aquadest. The results showed that bacteria can grow on media made of 20 gr/600 ml white canna tubers with the highest number of bacterial colonies of 9,5. 103 CFU/ml. This proves that white canna tubers are much more effective as a medium for growing bacteria compared to red canna tubers. Keyword: alternative media, bacterial growth media, Nutrient Agar, Canna edulis tuber